Pengembangan Media Pembelajaran Geografi Berbasis Aplikasi Prezi Di SMA Negeri 1 Suwawa Provinsi Gorontalo - Puluhulawa, Nur Fakriya; Maryati, Sri; Yusuf, Daud (-, 2024)
Development of Prezi Application-Based Learning Media in Geography Subjects, Material on Diversity of Indonesian Flora and Fauna." This research aims to develop Prezi-based application media in geography subjects, material on Diversity of Indonesian Flora and Fauna, class XI IPS at SMA Negeri 1 Suwawa. The Prezi application-based learning media was developed using the ADDIE development model, which consists of 5 stages, namely the analysis stage, planning stage, development stage, implementation stage and evaluation stage. Based on the research results, the validation value from product design experts received a value of 81.5% (very valid), validation from material/content experts with a value of 81.3% (very valid). Meanwhile, the validation value from subject experts was 88% (very valid). Results Evaluation of student responses (limited scale) in understanding the material presented reached 84.3%. Student responses (general scale) were 83.6% for learning media based on the Prezi application in the geography subject, Diversity of Indonesian Flora and Fauna at SMA Negeri 1 Suwawa, was declared to meet the requirements of good (Good) or suitable for use.